Contribution to the study of the compatibility of self-compacting repair mortar based on local materials reinforced with sisal fibers - Djamed, Anfal; Kouidri, Zohra, Directeur de thèse (My University, 2020)
Reinforced concrete is the most widely used material in the world, but is designed with a specific service life and deteriorate over time due to their exposure to environmental conditions. In order to increase the service life of concrete structures, they can sometimes be rehabilitated and repaired using repair materials. However, problems may develop between the repair material and old concrete due to differential deformation between them. Due to the availability of a wide variety of repair materials in the construction field with a wide range of physical and mechanical properties, it is important to determine the compatibility of a repair material with the old concrete. Good bond strength between overlay and substrate is a key factor in performance of concrete repair. The aim of this work is to study the compatibility of self-compacting repair mortars based on dune sand, limestone sand and sisal fibers. Compressive strength, flexural strength, shrinkage, elastic modulus, porosity and capillary water absorption of the repair materials were individually measured in the first part. In the second part, the compatibility was investigated using a pull-off, slant shear, and splitting tensile tests. Results indicate that elaborated repair mortars present excellent adhesion to the substrate compared to the Ready-Mixed Mortar (RMM)
Laghouat : Université Amar Telidji - Département d'architecture Option : Materials of Civil Engineering .